Family dynamics and childhood depression: An analysis of signs, risk factors and psychotherapeutic interventions at school age (Research, Society and Development, 2023)
Depression in childhood is a complex challenge to identify, as children are in full development and exposed to various environmental stimuli. Through a systematic review of the literature, this study addresses the need for a careful assessment focused on family dynamics in order to identify signs of depression in school-age children, since their behaviors and thoughts are different from those of adults. These signs encompass a variety of psychological factors, such as expressions of anger, irritation, disinterest and psychomotor and learning problems. Biological factors also play a role, including genetic predisposition and influences during pregnancy, such as trauma and substance use. In addition, social and economic factors, such as vulnerability, family relationships and the environment, have a direct impact on children's development. The family system can provide support, security and shelter, or trigger depressive disorders through neglect, lack of affective reciprocity, overprotection and activity overload. Children between the ages of 6 and 12 are especially focused on relationships and developing their own interests, making them susceptible to depression. Psychology intervenes in a preventive and therapeutic way, using approaches such as family therapy and psychoeducation (FPT) and interpersonal therapy (IPT) involving specialized listening and guidance for both children and their families, as well as targeting public policies aimed at vulnerability. In addition, in order for this disorder to be identified, prevented and better psychodiagnosed, more studies are needed to point out the particularities found in children.